Technical Efficiency Analysis of Cassava Farmers on Suboptimal Dry Land - Sri Ratna Triyasari; Moh. Wahyudi Priyanto (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
The government launched a food diversification program, one of which was cassava so that the population does not depend on rice, and anticipates when rice production decreases due to crop failure. However, cassava production was much lower than rice. There were efforts to utilize suboptimal land to increase cassava suplly for population consumption. Therefore, this study aimed to assess the level of technical efficiency of cassava farming on suboptimal dry land. The research sample of 60 cassava farmers in Jaddih Village, Bangkalan Regency was taken by census to answer the research objectives. Stochastic frontier analysis was used to determine the effect of agricultural inputs consisting of land, seeds, labor, costs, and manure on the production of cassava. Then to determine the effect of age, experience, formal education, non-formal education, and family dependents on cassava insufficiency. The results show that cassava production will increase with the increase in land area, but will decrease with the increase in seedlings. The average technical efficiency of cassava was 87%, where this value will increase if farmers attend non-formal education. This research contributes to policy makers to optimize suboptimal land use, and to farmers to take advantage of production inputs and socio-economic variables that affect production increases and technical efficiency.